FINITE ELEMENT ANALYSIS OF THE STEEL-CONCRETE COMPOSITE BEAM- COLUMN CONNECTION UTILIZING PREFABRICATED PERMANENT STEEL FORM - Gusmanova, Laura (Nazarbayev University School of Engineering and Digital Sciences, 2021)
The composite structural element is widely used nowadays due to performance compared with other traditional construction material usage. Composite member represents the combination of two main construction materials: steel and concrete where they act together as a single composite section. The Professor’s Deuckhang Lee Structural Engineering laboratory team proposed the comparatively new and beneficial structural design and the test on ten different designs was conducted at the multi-purpose experiment station in Songdo, South Korea. The proposed design represents the steel-concrete composite beam-column connections utilizing prefabricated permanent steel form (PPSF). In the thesis, the performance of this composite system is investigated based on experimental data conducted previously and an analytical study by FEM on the ABAQUS program. Five different design specimens are covered in this thesis. The differences in specimens are in the asymmetric section of the WFB, type of the column (SRC or H-type) and in the longitudinal reinforcement placement (anchorage or passing through the column). The analytical model of the composite beam-column connection was accomplished based on the dimensional details of the real performed test. The joint was modeled and meshed in ABAQUS software by utilizing 10-nodes tetrahedral element and 2-nodes linear beam elements for solid and truss part, respectively. In addition, the nonlinear material behavior of the concrete was taking into account in this model and the concrete damaged plasticity was assigned as concrete model. Interaction and load condition were assigned accordingly. First, static load was applied in order to obtain the backbone first for validation of the analysis model. From the comparison of the modeling results and test measurements it was found that both of them coincide with each other. Therefore, numerical analysis could be accomplished of the composite structure under static loading. In addition, the only steel part consisted of WFB and H-steel of the column was analyzed under cyclic loading and analysis showed that steel part buckled. The composite structure can improve the overall behavior of the beam-column joint and make its structural behavior stable by the composite effect. By comparing the FEM analysis results with test results for model under cyclic loading, the maximum error of the hysteresis curve is 22% for S5 specimen, results for all other specimens are in the range of the applicable percentage (<20%). This proves the reliability of the finite element model analysis. However, FEA modeling was not capable to catch the cyclic responses of specimens with H-type column differ slightly without catching strength degradation.
Keywords: prefabricated permanent steel form; Research Subject Categories::TECHNOLOGY; ABAQUS program; Type of access: Gated Access